2010
DOI: 10.1088/0957-4484/21/21/215501
|View full text |Cite
|
Sign up to set email alerts
|

H2sensing characteristics of SnO2coated single wall carbon nanotube network sensors

Abstract: SnO(2) nanoparticle coated single wall nanotube (SWNT) network sensors were fabricated by forming a SWNT network on the Pt patterned SiO(2)/Si substrate using a dip coating method and subsequently depositing SnO(2) nanoparticles on the SWNT network by rf magnetron sputtering. Their H(2) gas sensing properties were investigated. The SnO(2)-SWNT network sensors stably and reversibly responded to H(2) gas even at room temperature and could detect H(2) gas down to 100 ppm. In addition to the low temperature detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Consequently, the DMMP sensing behavior was changed from p-type to n-type with ZnO deposition time. Similar observation has been found in SnO 2 nanoparticle-coated SWNT network sensor toward H 2 gas [15]. To confirm the type change, Hall measurement was performed in Van der Pauw configuration (Ecopia21, Model: HMS-3000).…”
Section: Resultssupporting
confidence: 74%
“…Consequently, the DMMP sensing behavior was changed from p-type to n-type with ZnO deposition time. Similar observation has been found in SnO 2 nanoparticle-coated SWNT network sensor toward H 2 gas [15]. To confirm the type change, Hall measurement was performed in Van der Pauw configuration (Ecopia21, Model: HMS-3000).…”
Section: Resultssupporting
confidence: 74%
“…Many studies have demonstrated that more abundant metal oxides can be good candidates for replacing noble metals in designing sensor materials. Both n‐type (SnO 2 , TiO 2 , ZnO, and WO 3 ) and p‐type metal oxides (Co 3 O 4 and CuO) have been shown to contribute to the room‐temperature sensing abilities of CNTs, while SnO 2 seems to be the most investigated material.…”
Section: Materials For Gas Sensing21single‐element Materialsmentioning
confidence: 99%
“…[1][2][3] High temperature gas-sensing devices require effective gate contact structures for sensitivity of devices. 4 5 We then focus on carbon nanotubes (CNTs) due to their properties.…”
Section: Introductionmentioning
confidence: 99%